Chromatic aberration and spectral dependency of extended-range-of-vision intraocular lens technology - Łabuz, Grzegorz; Yan, Weijia; Baur, Isabella; Khoramnia, Ramin; Auffarth, Gerd U. (Scientific reports, 2023)
This study compared the optical quality and chromatic performance of refractive-diffractive intraocular lenses (IOLs) that are designed to extend the range of vision of pseudophakic patients and alter chromatic aberration. Five IOLs were evaluated, Tecnis Synergy and Triumf POD L GF, both intended to compensate for eye's chromatism, as well as Acriva Trinova Pro C—a lens that increases chromatic aberration, and AT Lisa Tri and AcrySof IQ PanOptix. An optical setup composed of a corneal model inducing monochromatic and chromatic aberrations and incorporating various spectral conditions was employed. The two chromatic-aberration correcting IOLs demonstrated the lowest far-focus dispersion, but it was negative only, with the Synergy indicating its ability to reduce eye’s chromatic aberration. Although the Trinova increased far-point chromatism, it was close to the level of the PanOptix, but higher than that of the AT Lisa. All the studied models demonstrated varying optical quality in response to light color. Still, the strongest spectral dependency was associated with achromatizing technology. Therefore, chromatic aberration and wavelength dependency should be considered in IOL optimization and predicting visual function, particularly in non-white spectral conditions.
Veröffentlicht: 07. September 2023
Gesehen am 20.11.2023